The Student Learning Outcomes in Science and Social Studies (IPAS): Picture Media at Primary School - Benselina Erlina Unawekla; Fransheine Rumtutuly; Jekriel Septory (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This research is motivated by the low learning outcomes of students in Natural and Social Sciences (IPAS) in the fourth grade of Kaiwatu Christian Primary School, Southwest Maluku Regency. This study aims to describe and analyze the improvement in IPAS learning outcomes through the application of image media using the Kemmis and McTaggart spiral model. The method used is Classroom Action Research (CAR) implemented in two cycles. The research subjects consisted of 16 fourth-grade students in the 2024/2025 academic year. Data collection techniques included learning outcome tests, observation, and documentation. The results showed a consistent positive trend in quantitative indicators at each stage. In the pre-cycle stage, the class average only reached 65 with a critical classical completion of 19% (3 students). After the intervention in Cycle I, the average score increased to 70 with a classical completion of 44% (7 students). Following reflection-based corrective actions in Cycle II—conducted through enrichment of image variations, intensification of visual-based question-and-answer sessions, and group strengthening—the class average jumped to 78 with an absolute classical completion rate of 100% (all 16 students met the learning objective achievement criteria). This study concludes that the application of image media successfully transforms the learning process from verbalistic and conventional into more visual, interactive, and contextual. Theoretically and practically, this visualization is highly effective in strengthening cognitive schemas and fostering active engagement for primary school students at the concrete operational stage.